A interação entre enforcement público e privado no direito concorrencial brasileiro - Leonel Moraes Barros (2021)
This master's thesis investigates the interaction between public and private enforcement in Brazilian Competition Law from the economic analysis of law. So, it seeks: (i) to understand what are public and private enforcement in the current context of stimulating the filing of actions for damages; (ii) the methods of quantification of damages; (iii) the public and private enforcement functions in the antitrust policy, especially regarding the deterrence and compensation of damage; (iv) and the possible existence of tension between both. In this sense, it noted that the possibility of using documentation obtained from public enforcement by the victims of anticompetitive conduct may generate imbalances in the antitrust policy, especially an impact on the use of leniency agreement as an instrument to the repressive role of the antitrust authority. Based on the investigation of other jurisdictions, it noted that the main solutions used to solve the abovementioned tension consist in limiting the leniency recipient's tort law and in attributing confidentiality to the evidence obtained in the leniency agreement. By application of game theory, it observed that the disclosure of evidence obtained by the competition authority to stimulate private enforcement could increase the deterrence of illegal practices by potential violators if the authority has the means to detect collusive practices. However, if the authority has a low skill to identify and punish cartels, evidence disclosure would discourage the leniency program. However, if the legal system provided for disclosure evidence and the subsidiary leniency recipient's tort law, the deterrence of collusion would occur if the ability to detect the cartel is not null.